MAIN SPECIES USED IN VENEER PRODUCTION IN CURITIBA, PR - NISGOSKI, Silvana; de MUÑIZ, Graciela Inés Bolzon; KLOCK, Umberto (Scientia Agraria, 2000)
This work is about identification of main species used in veneer production in Curitiba, Parana State, Brazil, and popular names variation, for a correct identification. Seventy two sliced veneers and rotary cut veneers samples, from species based on frequency and utilization importance, were collected. Because of samples characteristics, the identification was based in peculiar structures. Thirty seven species were identified. Incorrect commercial names in association to botanical names were verified. Identification technics adoption, based on anatomic characteristics, and nomenclature standard, using papers made by competent members, are necessary.